An epidermal growth factor receptor-targeting immunotoxin based on IgG shows potent antitumor activity against head and neck cancer - Huang, Mei; Park, Jisoo; Seo, Jina; Ko, Sanghwan; Yang, Yoon Hee; Lee, Yeaji; Kim, Hyo Jeong; Lee, Bok Soon; Lee, Yun Sang; Ko, Byoung Joon; Jung, Sang Teak; Park, Deachan; et al. (FASEB Journal, 2024)
The epidermal growth factor receptor (EGFR) is an important target for cancer therapies. Many head and neck cancer (HNC) cells have been reported to overexpress EGFR; therefore, anti-EGFR therapies have been attempted in patients with HNC. However, its clinical efficacy is limited owing to the development of drug resistance. In this study, we developed an EGFR-targeting immunotoxin consisting of a clinically proven anti-EGFR IgG (cetuximab; CTX) and a toxin fragment (LR-LO10) derived from Pseudomonas exotoxin A (PE) using a novel site-specific conjugation technology (peptide-directed photo-crosslinking reaction), as an alternative option. The immunotoxin (CTX-LR-LO10) showed specific binding to EGFR and properties of a typical IgG, such as stability, interactions with receptors of immune cells, and pharmacokinetics, and inhibited protein synthesis via modification of elongation factor-2. Treatment of EGFR-positive HNC cells with the immunotoxin resulted in apoptotic cell death and the inhibition of cell migration and invasion. The efficacy of CTX-LR-LO10 was evaluated in xenograft mouse models, and the immunotoxin exhibited much stronger tumor suppression than CTX or LR-LO10. Transcriptome analyses revealed that the immunotoxins elicited immune responses and altered the expression of genes related to its mechanisms of action. These results support the notion that CTX-LR-LO10 may serve as a new therapeutic agent targeting EGFR-positive cancers.
Keywords: ADP Ribose Transferases; Animals; Antineoplastic Agents; Apoptosis; Bacterial Toxins; Cell Line, Tumor; Cell Movement; Cetuximab; ErbB Receptors; Exotoxins; Female; Head and Neck Neoplasms; Humans; Immunoglobulin G; Immunotoxins; Mice; Mice, Inbred BALB C; Mice, Nude; Pseudomonas aeruginosa Exotoxin A; Virulence Factors; Xenograft Model Antitumor Assays; antibody-drug conjugate; cetuximab; epidermal growth factor receptor; head and neck cancer; immunotoxin; peptide-directed photo-crosslinking